2010
DOI: 10.1016/j.rmed.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Sniff nasal inspiratory pressure versus IC/TLC ratio as predictors of mortality in COPD

Abstract: The SnIP conveys at least as much predictive power for mortality in COPD as hyperinflation determined by IC/TLC ratio. This test is cheaper, quicker and easier than measuring lung volumes by plethysmography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 30 publications
(26 reference statements)
1
27
0
14
Order By: Relevance
“…The lack of difference in BMI between survivors and nonsurvivors in the nonatelectasis group suggests that it was not a significant factor determining survival, and it is unlikely to be the explanation for the marked difference in outcome we observed. Moreover, in a study from our group based on a similar hospital-based COPD cohort, following 110 patients with a mean FEV1 of 36.6% pred for f5 yrs, BMI did not differ between those who had died (n537) and survivors (n573) (25¡6.4 versus 25.1¡6.4 kg?m -2 , respectively) [24].…”
Section: Significance Of Findingsmentioning
confidence: 74%
See 1 more Smart Citation
“…The lack of difference in BMI between survivors and nonsurvivors in the nonatelectasis group suggests that it was not a significant factor determining survival, and it is unlikely to be the explanation for the marked difference in outcome we observed. Moreover, in a study from our group based on a similar hospital-based COPD cohort, following 110 patients with a mean FEV1 of 36.6% pred for f5 yrs, BMI did not differ between those who had died (n537) and survivors (n573) (25¡6.4 versus 25.1¡6.4 kg?m -2 , respectively) [24].…”
Section: Significance Of Findingsmentioning
confidence: 74%
“…Successful BLVR, where atelectasis occurred, is likely to have mimicked the effects of LVRS by reducing operating lung volumes. Measures of gas trapping inspiratory capacity/total lung capacity ratio [27] and sniff nasal pressure [24] have been shown to be associated with mortality in COPD, and both lung volumes and diaphragm function improved most in the atelectasis patients [14]. Dynamic hyperinflation also improved most in patients with atelectasis.…”
Section: Significance Of Findingsmentioning
confidence: 99%
“…are evaluated including FEV 1 (33), carbon monoxide transfer (34), hyperinflation (35), and 6MW distance (36) no differences were observed between patients with and without PFO. These data are consistent with the observation that oxygen, except in high doses, does not extend exercise performance in COPD (37,38).…”
Section: Original Articlementioning
confidence: 99%
“…They also state that inspiratory muscle weakness contributes to a range of poor outcomes in COPD, whereas in our view associations between reduced inspiratory pressures due to hyperinflation and poor outcomes may simply be epiphenomena. Thus, for example, in a recent survival analysis [10] we found that both inspiratory muscle strength and hyperinflation predicted death in a substantially similar way, probably because they measured different properties of the same thing. In fact, inspiratory muscle strength proved statistically, but not clinically, superior with an area under the curve on a receiver operating characteristic plot of 0.68 versus 0.62 compared with inspiratory capacity/total lung capacity ratio, but the possible technical factors, notably transmission of pressure within the emphysematous lung, underlying this are beyond the scope of this editorial.…”
mentioning
confidence: 68%